A Short Measure of Acceptability of Intimate Partner Violence Against Women: Development and Validation of the A-IPVAW-8 Scale. (July 2022) - Martín-Fernández, Manuel; Gracia, Enrique; Lila, Marisol
Attitudes of acceptability of intimate partner violence against women (IPVAW) are considered one of the main risk factors of this type of violence. The aim of this study is to develop and validate a short version of the acceptability of IPVAW scale, the A-IPVAW-8, for large scale studies where space and time are limited. A panel of experts were asked to assess item content validity. Two samples were recruited to assemble an 8-item short version of the scale using automated test assembly, and to reassess the psychometric properties of the A-IPVAW-8 in an independent sample. Results showed that the A-IPVAW-8 had adequate internal consistency (α = .72-.76, ω = .73-.81), a stable one-factor latent structure (comparative fit index [CFI] = 0.94, Tucker–Lewis index = 0.92, root mean square error of approximation = 0.077), validity evidences based on its relationships to other variables in both samples, and was also invariant across gender (ΔCFI < |0.02|). This study provides a short, easy-to-use tool to evaluate attitudes of acceptability of IPVAW for large scale studies.